Role of NINJ1 in Gout Flare and Potential as a Drug Target - Zhang H; Gao J; Fang W; Tang Y; Fang X; Jin T; Tao J (Dove Medical Press, 2022)
Hongliang Zhang,1 Jie Gao,1 Wenxiang Fang,1 Yujie Tang,1 Xuan Fang,1 Tengchuan Jin,2 Jinhui Tao1 1Department of Rheumatology and Immunology, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People's Republic of China; 2Laboratory of Structural Immunology, CAS Key Laboratory of Innate Immunity and Chronic Disease, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, 230001, People's Republic of ChinaCorrespondence: Jinhui Tao; Tengchuan Jin, Email taojinhui@ustc.edu.cn; jint@ustc.edu.cnObjective: To determine the role of nerve injury-induced protein 1 (NINJ1) introduced plasma membrane rupture (PMR) and damage-associated molecular patterns (DAMPs) release in the pathogenesis and progression of gout and to explore the potential of NINJ1 as a therapeutic target in gout.Methods: Both peripheral blood mononuclear cells (PBMCs) and serum sample from gout patients (n = 58) and healthy controls (n = 16) were collected and processed to NINJ1 expression, lactate dehydrogenase (LDH) detection, NINJ1 inhibition, and NINJ1 expression experiments, respectively. NINJ1 knockdown was carried out by lentivirus in a monosodium urate (MSU) induced rat model, and NINJ1 neutralizing antibody was applied in a MSU induced mouse model.Results: Our results found that NINJ1 was upregulated during a gout flare, and the resulting induction of PMR correlated with gout progression. NINJ1 knockdown significantly reduced the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome activation and joint swelling in the rat model, and NINJ1 neutralizing antibody also significantly reduced gout flare in the mouse model and PBMCs. Moreover, NINJ1 expression is under NLRP3 inflammasome produced interleukin (IL)-1β control.Conclusion: These results support the notion of a pathogenic role of NINJ1 introduced PMR in gout and provide a detailed mechanism for gout pathogenesis involving inflammatory cell death and DAMPs release introduced by IL-1β. In addition, targeting NINJ1 might be a potential therapeutic approach for gout.Keywords: gout arthritis, NINJ1, NLRP3 inflammasome, plasma membrane rupture, therapeutic target